The Management Model of Organizational Space Based on Quranic Doctrines - Mahdi Zirak; Sayyid Jafar Alavi; Hojjat Gohari (آموزه‌های قرآنی)
The human living environment in which human relationships are formed is one of the influential factors that is very important in terms of having special characteristics in human life and it can be said that environmental management is the most effective way to achieve organizational success. Therefore, we will express a three-step model in the following, for managing the environment in a desirable way and executive strategies that are based on Quranic doctrines, because we believe that the Qur'an is a complete plan for human life and has a high importance to this factor of success. This model consists of three stages: environment selection, reformation and protection of the environment (space, area) and expanding the environment, in the first step, the manager tries to arrange the parts of the environment in the best way to create a healthy environment, but if this is not done properly, the manager focuses his efforts on reforming it and then seeks to maintain his healthy environment (space) and at the end after the stability of the environment, the manager takes a step further and tries to expand his suitable environment, so that other organizations can continue in this appropriate space.